Designing a Prototype User Interface Website into Mobile Form using the Goal-Directed Design Method (Case Study: Population Administration Service Website) - Wirayuda, I Made Bagus Surya; Sukarsa, I Made; Rusjayanthi, Ni Kadek Dwi; Wisswani, Ni Wayan (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol 12 No 2 (2024): Vol. 12, No. 2, August 2024, 2024)
The Population and Civil Registration Office in an Indonesian district has introduced a web-based service system that enables easy access for the public anytime and anywhere. This website offers services such as birth certificate issuance, electronic ID cards (e-KTP), and various other civil registration documents. Despite advancements in service delivery, challenges persist, particularly regarding inadequate interface design that often confuses users. Through heuristic evaluation, it was found that 12 aspects require improvement with average scores below 2.50. Therefore, a redesign is necessary to address user interface issues. The redesign employs the Goal-Directed Design (GDD) method to provide better recommendations for website development. Following these improvements and subsequent heuristic evaluations, there was a significant increase in average improvement scores, reaching 4.13.